2021
DOI: 10.3390/children8020166
|View full text |Cite
|
Sign up to set email alerts
|

Important Aspects Influencing Delivery of Serious News in Pediatric Oncology: A Scoping Review

Abstract: Delivering serious news presents a major challenge for clinical practice in pediatric oncology due to the complexity of the communication process and a number of aspects that influence how the serious news is delivered and received. This study aims to review and explore the aspects influencing the delivery of serious news in pediatric oncology from the perspective of physicians, parents, siblings and patients themselves. The MEDLINE, Embase, Scopus, Cochrane Library, PsycInfo and Medvik databases were systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Again, it is important to consider that both diagnosis and prognosis may have been communicated by healthcare professionals several times, yet were not perceived as communicated by parents, possibly due to the extremely stressful situation. In a recent scoping review regarding communicating bad news in childhood cancer care, it was found that parents were sometimes so troubled and upset that this decreased their ability to listen to and understand the information delivered by physicians 19 . Healthcare professionals may therefore need to regularly assess how well‐informed the child and parents are and repeat important information if needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, it is important to consider that both diagnosis and prognosis may have been communicated by healthcare professionals several times, yet were not perceived as communicated by parents, possibly due to the extremely stressful situation. In a recent scoping review regarding communicating bad news in childhood cancer care, it was found that parents were sometimes so troubled and upset that this decreased their ability to listen to and understand the information delivered by physicians 19 . Healthcare professionals may therefore need to regularly assess how well‐informed the child and parents are and repeat important information if needed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent scoping review regarding communicating bad news in childhood cancer care, it was found that parents were sometimes so troubled and upset that this decreased their ability to listen to and understand the information delivered by physicians. 19 Healthcare professionals may therefore need to regularly assess how well‐informed the child and parents are and repeat important information if needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is also vital to communicate effectively in order to convey accurate information to patients and their families, so that they can make an informed decision about their healthcare. However, disclosing the diagnosis of a serious illness or the poor prognosis of a disease often represents a daunting task for physicians and a life-changing event for patients and their families [ 1 , 2 ]. In the past, before the 1960s, when clinicians began to promote a more open approach regarding communication with their patients, most literature recommended protecting patients, especially pediatric patients, in order to shield them from distress [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Now, open communication, which sheds light upon diagnosis and prognosis and includes the child’s parents in the care team, is a much more widely used approach. Recent studies have shown the benefits of discussing the diagnosis with pediatric patients themselves, using age-appropriate language [ 1 , 4 , 5 ]. This, in return, eases the burden on the parents of having to maintain a façade and opens a channel for the child through which he or she can raise questions and voice opinions [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation